Design and research of indoor wellness space under the concept of communication studies - Zhang, Weiwei; Rungsrisawat, Somdech (Edelweiss Applied Science and Technology, 2025)
This study investigates how communication theory can enhance indoor wellness space design, aiming to (1) identify key design elements influencing user satisfaction and (2) explore user experiences to improve engagement. A mixed-methods approach was employed, combining quantitative surveys (N=409) with qualitative focus groups and interviews (N=30) in Nanjing’s Gulou District. Quantitative analysis revealed that educational interactivity, aesthetics, and entertainment significantly predict satisfaction, with entertainment being the strongest driver of revisit intention. Qualitative findings uncovered four critical themes: interactive education, aesthetic personalization, entertainment integration, and information coherence, emphasizing the need for dialogic communication, culturally resonant design, dynamic activities, and clear messaging. The study concludes that wellness spaces must move beyond standardized, passive models toward adaptive, user-centered designs that foster engagement through multisensory and participatory experiences. The novelty of this research lies in its integration of communication studies with environmental design, offering a theoretical and practical framework for creating therapeutic, communicative wellness spaces.